Major Depressive Disorder and Alterations in Insular Cortical Activity: A Review of Current Functional Magnetic Imaging Research - Sliz, Diane; Hayley, Shawn (Frontiers in Human Neuroscience, 2012)
Major depressive disorder (MDD) is characterized by a dysregulated fronto-limbic network. The hyperactivation of limbic regions leads to increased attention and processing of emotional information, with a bias toward negative stimuli. Pathological ruminative behavior is a common symptom of depressive disorder whereby the individual is unable to disengage from internal mental processing of emotionally-salient events. In fact, lower deactivations of the neural baseline resting state may account for the increased internal self-focus. The insular cortex, with its extensive connections to fronto-limbic and association areas has recently also been implicated to be a part of this network. Given its wide-reaching connectivity, it has been putatively implicated as an integration center of autonomic, visceromotor, emotional and interoceptive information. The following paper will review recent imaging findings of altered insular function and connectivity in depressive pathology.